Monoclonal gammopathy of undetermined significance: a new proposal of workup. (17th August 2013) - Mangiacavalli, Silvia; Cocito, Federica; Pochintesta, Lara; Pascutto, Cristiana; Ferretti, Virginia; Varettoni, Marzia; Zappasodi, Patrizia; Pompa, Alessandra; Landini, Benedetta; Cazzola, Mario; Corso, Alessandro
Abstract: Objective: Diagnostic criteria for monoclonal gammopathy of undetermined significance (MGUS) require quantification of bone marrow plasma cells (BMPCs) and skeletal survey to discriminate between MGUS and multiple myeloma (MM). By contrast, recent published guidelines suggest that these procedures could be avoided in the presence of serum monoclonal spike (M‐spike) of small amount (≤1.5 g/dL). Aim of this study is to better quantify the risk of missing a diagnosis of MM, not performing bone marrow aspirate and skeletal survey in patients with M‐spike ≤ 1.5 g/dL asymptomatic for bone pain. Methods: We reviewed data of 2282 patients consecutively observed from January 1974 to December 2010 in our single hematology department. We considered eligible for this study 1271 patients with grade <2 NCI bone pain, confirmed to have an MGUS or an MM after extensive standardized diagnostic workup including bone marrow biopsy, skeletal bone survey and laboratory tests. Results: The risk of finding a BMPC infiltration ≥10% in patients with an M‐spike ≤ 1.5 g/dL was very low (7.3%), although significantly different according to IgH isotype (4.7% for IgG vs. 20.5% for IgA). The risk of finding bone lesions with M‐spike ≤ 1.5 g/dL was negligible (2.5%), regardless of IgH isotype. Conclusion: In asymptomatic patients with M‐spike of small amount (≤1.5 g/dL): (i) BMPC evaluation may be reasonably avoided in patients with IgG M‐spike, while should always be part of diagnostic workup in the presence of IgA M‐spike and (ii) skeletal survey, less predictive for MM, should not be routinely indicated irrespective of IgH isotype.